Academic networks and research groups in Iberoamerica (2022)
Volume 24, number 39 of the Journal of the History of Latin American Education -RHELA, recovers the memory of the Argentine teacher Olga Cossettini (1898-1987), pioneer of the Escuela Nueva in Santa Fe- Argentina, and is dedicated to "Academic and research networks." Rhela is by antonomasia the expression of the periodical publication of the Society for the History of Latin American Education (SHELA), so it is a commitment to present the progress of the networks that have been generated from this and alternative networks. In this sense, it is an experience that combines the work of research groups and networks, to present the results and the rate of social return of the same. Within the framework of the 30 years of the Hisula Group -UPTC (1992-2022), it is a commitment to present the productivity on the subject under study, since it has been the manager of networked knowledge. It is a necessary and urgent study, at a time when artificial intelligence challenges the production of knowledge resulting from research projects and with foundations in vulnerable and resilient contexts. The monograph begins with a monographic study of the teacher Olga Cossettini (1898-1987), by the researcher of the National University of Córdoba, María Cristina Vera de Flachs. It is a study that unravels the life history of teacher Olga Cossettini, with a long career in the province of Santa Fe, from the Cossettini Pedagogical Archive. The contribution translates into a resizing of the methodology of the Active School in a modality that she defined as the Serene School.